Análise de situações de aprendizagem envolvendo números racionais: uma abordagem para o ensino de argumentações e provas na matemática escolar - Pereira, Marcelo Eduardo (2007)
The purpose of this research is to analyze learning situations concerning argumentations and mathematical proofs combined with a computational tool and had been developed into the AprovaME project - Argumentação e Prova na Matemática Escolar (Argumentation and Proof in School Mathematics), particularly during the second phase. We are founded by researches that explore the assuming functions of proof as well as evaluate them in the school context, underneath various aspects and generality levels. Guided by the main results of this studies and the survey of proof conceptions made by the teenager students that had been accomplished during the first phase of the project, we prepared a sequence of activities intending to engage them throughout the stages of proving and to argue about the conditions of transiting between pragmatic and conceptual proofs. We search, into this context, to explore different functions proof, beyond the verification one, and to analyze the role of the Microsoft Excel tool in the students empirical work. The activities were applied in extra classes sessions for three pairs of volunteer students between 15-16 years old from a private school in Santos-SP. As result, it was verified that students interaction with the computer had dynamized the process of surveying conjectures and validating them. Also through the computer experience they were able to notice the manipulated objects properties which developed the production of justifications beyond empirical evidences. Therefore, within this proposal, the students had experienced the moments of proving and presented, by deductive reasoning, argumentations that show clearly the generality involved in the suggested tasks